ATTITUDE TOWARD KOREAN CELEBRITIES VS INDONESIA CELEBRITIES: WHICH ONE HAS A STRONGER EFFECT ON PURCHASE INTENTION? - Keni Keni; Nicholas Wilson (Universitas Gunadarma, 2026)
This study aimed to assess the impact of attitudes toward Korean and Indonesian celebrities, perceived behavioral control, and subjective norms on consumers’ purchase intentions. This research employs a closed-ended online questionnaire to investigate the factors influencing purchase intentions for products endorsed by both Korean and Indonesian celebrities. A total of 323 respondents who had purchased products endorsed by both Korean and Indonesian celebrities within the last three months filled in the questionnaire. To ensure data relevance, a purposive sampling technique was employed, enabling authors to select participants with relevant experiences who could provide meaningful insights into the research objectives. After a thorough review, 46 responses were excluded because they did not meet the established eligibility criteria, resulting in 287 valid responses for further analysis. These data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 software. Findings obtained in this study confirmed that all variables significantly and positively affect purchase intentions, with attitudes toward Korean celebrities exhibiting a more substantial influence than those toward Indonesian counterparts, thereby underscoring the decisive role of Korean celebrity endorsements in shaping consumer behavior.